The Impact of Mores on the Major Characters Life in Ibsens Ghost - R. Widya Yudha Prawita; Ni Luh Putu Rosiandani (Universitas Sanata Dharma, 2014)
This study examines the presence of mores as one aspect which constructs the social life in society as portrayed in Ibsens Ghosts. The mores as a manifestation of societys demands become important key aspect which may give influence in ones life in his efforts to build social interaction within the community. Through the mores, the societys expectation of ideal social situation is being projected. Some problems have been formulated as follows to see the way the major characters deal with the mores and the impact that may occur in their life. Firstly, it observes how the major characters are presented and what are the mores practiced. Secondly, it discusses what the impact of the mores on the major characters life that comes out as the result of major characters responses toward the mores. Based on the analysis, it shows that characters characteristics are various. The obdurate and conservative characteristic can be seen through Manders while Mrs. Alving is presented as an openminded and critical though she seems like a doubter. Being different is Oswald which is more expressive, liberal and rebellious. The various kinds of characteristics above have significant role in the way a character response the demands of the society (the mores). Meanwhile in the world of reality, sometimes what is considered as an ideal in mores is not always appropriate to be applied in the real condition. This dilemma may lead some people to give various responses or even behave recklessly in dealing with mores. Then, consequently, whatever the response taken or shown by the people in responding the mores at last will bring a new impact in their life as an individual. Keywords: the mores, society, social life